Pengaruh Tax Avoidance, Kepemilikan Asing, Tingkat Implementasi IFRS dan Profitabilitas Terhadap Nilai Perusahaan - Denada Febiola; Ahalik (UNIVERSITAS KALBIS, 2022)
The purpose of this study was to examine the effect oh tax avoidance, foreign ownership, the level of IFRS implementation and profitability on firm value. The study was conducted on LQ 45 companies that were consistently listed on the Indonesia Stock Exchange in 2015-2018. The number of samples obtained was 30 companies using purposive sampling method and the amount of research data obtained was 120. The data analysis method used is multiple linier regression. Simultaneous test result indicate that tax avoidance, foreign ownership, the level of IFRS implementation and profitability simultaneously affect the firm’s value. The partial test results show that tax avoidance, foreign ownership and the level of IFRS implementation have no effect on firm value, while profitability has a positive effect on firm value.